2001
DOI: 10.1038/sj.onc.1204993
|View full text |Cite
|
Sign up to set email alerts
|

Candidate tumour suppressor genes at 11q23–q24 in breast cancer: evidence of alterations in PIG8, a gene involved in p53-induced apoptosis

Abstract: One of the most consistently deleted chromosomal regions in solid tumours is 11q23 ± q25, which consequently has been postulated to harbour one or more tumour suppressor loci. Despite large eorts to identify the responsible genes, the goal remains elusive, but as knowledge accumulates new candidates are emerging. The present study was undertaken in an attempt to assess the possible implication of four genes residing at 11q23 ± q24, in a population of early onset breast cancer (n=41). The coding sequence of PIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…However, in PTT analysis, mutation in EI24 was detected in 17% (7/41) of the breast cancer samples. 19 Sequencing analysis of the exons also revealed the presence of major alleles only in the SNPs present in CHEK1 exon 10: rs34097480 (G/A), rs2847422 (C/T) and EI24 exon 3: rs11538202 (A/G), rs1043914 (G/C). However, more samples should be analyzed to find out the association of these SNPs with this tumor.…”
Section: Mutation Is a Rare Event For Chek1 Ei24 And Loh11cr2amentioning
confidence: 97%
See 2 more Smart Citations
“…However, in PTT analysis, mutation in EI24 was detected in 17% (7/41) of the breast cancer samples. 19 Sequencing analysis of the exons also revealed the presence of major alleles only in the SNPs present in CHEK1 exon 10: rs34097480 (G/A), rs2847422 (C/T) and EI24 exon 3: rs11538202 (A/G), rs1043914 (G/C). However, more samples should be analyzed to find out the association of these SNPs with this tumor.…”
Section: Mutation Is a Rare Event For Chek1 Ei24 And Loh11cr2amentioning
confidence: 97%
“…16,18 PTT analysis revealed 9% mutation of this gene in breast cancer. 19 However, no such association of LOH11CR2A with CACX has yet been reported. Within 1.5 Mb telomeric to LOH11CR2A lies a cluster of candidate TSGs, such as ROBO3, ROBO4, EI24 and CHEK1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is yet unclear whether PIGs may act as tumor-suppressor genes or not. Gentile et al 6 reported that 16 (39%) of 41 primary breast cancers contained either deletion or single-base substitutions in PIG8. The study did not show whether the other allele of the PIG8 locus was lost or mutated or whether its mRNA or protein level was altered.…”
Section: Discussionmentioning
confidence: 99%
“…Among 108 candidate cancer-related genes, we focused on PIG7/LITAF for the following reasons: (i) higher expression of it was observed in 3 of 4 EMPD lesions examined, indicating that it could be involved in the common EMPD carcinogenesis pathway; (ii) mutation or dysfunction of other PIG genes has been suspected in human internal cancers; [5][6][7] and (iii) it was identified as the causative gene for CMT1C, which is an autosomal dominant disease with peripheral nerve degeneration, and its mutation is implied to cause aberrant proliferation and apoptosis in Schwann cells. 8 Considering PIG genes are the important mediators in the p53-induced apoptotic pathway, 9 PIG7/LITAF could be a candidate gene for involvement in EMPD carcinogenesis.…”
mentioning
confidence: 99%